A novel probiotic formula, BLLL, ameliorates chronic stress-induced depression-like behaviors in mice by reducing neuroinflammation and increasing neurotrophic factors - Ye, Minxiu; Ji, Feng; Huang, Chao; Li, Fu; Zhang, Changliang; Zhang, Yu; Wang, Runxin; Ma, Kai; Lu, Xu; Wang, Hui (Frontiers in Pharmacology, 2024)
Probiotics have been recognized for their various biological activities, including antioxidant and anti-inflammatory properties. This study investigates the therapeutic effect of a novel probiotic formula, BLLL, consisting of Bifidobacterium breve, Lactobacillus plantarum, Lactobacillus paracasei, and Lactobacillus helveticus, on chronic stress-induced depression-like behaviors in mice.The BLLL formula or phosphate-buffered saline (PBS) was given orally at a dose of 2, 4, or 8 ×10 10 CFU/kg once daily for 10 days in mice treated with chronic unpredictable stress (CUS) treated or vehicle. Depression-like behaviors were assessed using the sucrose preference test (SPT), the forced swimming test (FST), and the tail suspension test (TST). The mRNA and/or protein expression of interleukin-1β (IL-1β), IL-6, tumor necrosis factor-α (TNF-α), IL-4, IL-10, and chitinase-3-like protein 3 (CHI3L1, also known as Ym-1), as well as the concentration of nitrite, malondialdehyde (MDA), glutathione (GSH), and brain-derived neurotrophic factor (BDNF) in the hippocampus and medial prefrontal cortex were examined.The BLLL formula treatment at a dose of 8 × 10 10 CFU/kg, but not at a dose of 2 or 4 × 10 10 CFU/kg, improved CUS-induced depression-like behaviors in mice, as shown by the decrease in immobility time in the TST and FST and the increase in sucrose intake in the SPT. Further analysis revealed that BLLL treatment suppressed the CUS-induced increase in IL-1β, IL-6, and TNF-α mRNA and protein levels, as well as the CUS-induced decrease in IL-4, IL-10, and Ym-1 mRNA and/or protein levels in the hippocampus and medial prefrontal cortex. In addition, treatment with the BLLL formula countered the CUS-induced increase in nitrite and MDA levels and the CUS-induced decrease in GSH content and BDNF concentration in the hippocampus and medial prefrontal cortex.These results demonstrate that the novel probiotic formula BLLL ameliorates chronic stress-induced depression-like behavior in mice by suppressing neuroinflammation and oxido-nitrosative stress in the brain.